Letter to Jane Tolmach from Lee Nichols - Lee Nichols:::::: (1961)
A letter from Lee Nichols, Associate Press Secretary for Radio and Television, to Jane Tolmach regarding a tape that was sent to them. Nichols states that they will listen to the tape when Governor Brown returns from a trip to Washington.